Case report: Going through pregnancy safely after twice partial nephrectomy for bilateral kidneys with HLRCC-associated RCC - Dai, Kunhan; Jiang, Wencheng; Chen, Siyu; Luo, Shengjun; Ding, Siwei; Wang, Delin (Frontiers in Oncology, 2022)
Background HLRCC-associated RCC (hereditary leiomyomatosis and renal cell cancer-associated renal cell carcinoma) caused by germline mutations of fumarate hydratase (FH) gene is a rare autosomal dominant genetic renal cancer. At present, there are no reports of bilateral kidneys with HLRCC-associated RCC, let alone safe pregnancy after twice partial nephrectomy for bilateral kidneys HLRCC-associated RCC. Case presentation We report a 25-year-old female with bilateral renal tumors detected by ultrasound screening during a routine checkup. CT revealed a soft tissue mass in the parenchyma of the left kidney and a nodular soft tissue mass in the lower pole of the right kidney. She underwent robot-assisted laparoscopic left partial nephrectomy, and underwent laparoscopic right partial nephrectomy 3 months after first surgery. Heterozygous mutation in the FH gene on the patient's tumor tissue was detected by genetic testing. Combined with the patient's medical history, microstructure and immunohistochemical staining of tumor tissue and genetic test results, the pathological reports after two operations concluded HLRCC-associated RCC. Then she was injected with interferon and Nivolumab as a preventative treatment against tumor recurrence. Up to 38 months after surgery, having given birth to a baby, till now there was no tumor progression. Conclusions This is a clinically significant case, as it provides a reference for pregnancy in patients undergoing partial nephrectomy for bilateral kidneys with HLRCC-associated RCC and may indicate an effective approach to prevent tumor recurrence by Nivolumab in patients with HLRCC-associated RCC.